2020
DOI: 10.1002/jnr.24584
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and psychiatric disorders‐related axonal degeneration in Parkinson's disease

Abstract: Neurocognitive and psychiatric disorders have significant consequences for quality of life in patients with Parkinson's disease (PD). In the current study, we evaluated microstructural white matter (WM) alterations associated with neurocognitive and psychiatric disorders in PD using neurite orientation dispersion and density imaging (NODDI) and linked independent component analysis (LICA). The indices of NODDI were compared between 20 and 19 patients with PD with and without neurocognitive and psychiatric diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 67 publications
5
21
1
Order By: Relevance
“…In this study, only ICVF and AVF showed performance with AUC of over 0.80 among the NODDI and g-ratio analysis, respectively. This does not conflict with a previous study [25], which reported reduction of ICVF in white matter indicating axonal degeneration in PD.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In this study, only ICVF and AVF showed performance with AUC of over 0.80 among the NODDI and g-ratio analysis, respectively. This does not conflict with a previous study [25], which reported reduction of ICVF in white matter indicating axonal degeneration in PD.…”
Section: Discussioncontrasting
confidence: 57%
“…In this prospective study, which was approved by our institutional review board, MRI data of patients with PD and healthy controls were analyzed. There is subject overlap (64 out of 230) with previous studies [25,26], which used different analyzing methods (tract-of-interest, tract-based spatial statistics, and gray matter-based spatial statistics analyses) from the current study. Those studies did not use deep learning technique or connectome matrices in the evaluations of PD.…”
Section: Methodsmentioning
confidence: 99%
“…However, towards the changes of white matter microstructure in PD, the alterations of FA and MD due to PD remain controversial. Most studies focusing on advanced-stage PD patients reported decreased FA and/or increased MD, indicating demyelination and axonal degeneration of white matter microstructure 51 . Other results like increased FA and decreased MD were defined as microstructural compensation in prodromal-stage and early-stage of PD, which was distinguished from pathological findings 52 .…”
Section: Discussionmentioning
confidence: 99%
“…PD is associated with a wide variety of non-motor symptoms. Patients with PD who experience neurocognitive and psychiatric disorders (i.e., cognitive impairment, hallucinations, depression, anxiety, apathy, and dopamine dysregulation syndrome) exhibit broader axonal loss (indexed by ICVF), predominantly in the posterior regions of the WM, compared to those without these symptoms ( Figure 11 ) [ 127 ]. Using linked independent component analysis, Andica et al [ 127 ] demonstrated that ICVF was the highest contributor to diagnosis (59% weight) when compared to the DTI metrics (FA, MD, AD, and RD), ODI, and WM volume.…”
Section: Applications Of Advanced Diffusion Mri Techniques In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Tracts obtained using the ICBM-DTI-81 white matter tractography atlas ( B ). Abbreviations: ATR, anterior thalamic radiation; FA, fractional anisotropy; HC, healthy control; ICVF, intracellular volume fraction; IFOF, inferior fronto-occipital fasciculus; ILF, inferior longitudinal fasciculus; MD, mean diffusivity; PD-woNCPs, Parkinson’s disease without neurocognitive and psychiatric symptoms; PD-wNCPs, Parkinson’s disease with neurocognitive and psychiatric symptoms; RD, radial diffusivity; SLF, superior longitudinal fasciculus; UF, uncinate fasciculus (adapted and reproduced with permission from Andica et al [ 127 ]).…”
Section: Figurementioning
confidence: 99%